11p+19q+p-3q-6p=

Simple and best practice solution for 11p+19q+p-3q-6p= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 11p+19q+p-3q-6p= equation:


Simplifying
11p + 19q + p + -3q + -6p = 0

Reorder the terms:
11p + p + -6p + 19q + -3q = 0

Combine like terms: 11p + p = 12p
12p + -6p + 19q + -3q = 0

Combine like terms: 12p + -6p = 6p
6p + 19q + -3q = 0

Combine like terms: 19q + -3q = 16q
6p + 16q = 0

Solving
6p + 16q = 0

Solving for variable 'p'.

Move all terms containing p to the left, all other terms to the right.

Add '-16q' to each side of the equation.
6p + 16q + -16q = 0 + -16q

Combine like terms: 16q + -16q = 0
6p + 0 = 0 + -16q
6p = 0 + -16q
Remove the zero:
6p = -16q

Divide each side by '6'.
p = -2.666666667q

Simplifying
p = -2.666666667q

See similar equations:

| 3(2x-5)=27 | | x+(x+6)+12=66 | | 71-2x=34x+23 | | 14m+6n-4m+7n= | | (x+6)+12=66 | | 14-7x=110-35x | | 6a+1=2a+25 | | X^2-71*x+72=0 | | 2x+3=19+x | | -26-7x=110-35x | | -3x^2=-12 | | 180-7x=20x+21 | | 9t-3=8t-18 | | 7y+3=12y+8 | | -155-7x=10x+15 | | -155-7x=10x+25 | | 18+4y=18 | | 8x^2+3x+10=0 | | 6n-7=3n+2 | | 5x-18=22 | | 3x+7x=8 | | 3n+6=n+10 | | 7x^2-6x-111=0 | | 4.4x+3.8=13.2 | | 4x+34=12x-38 | | 4*0.5-3y=11 | | 2x+9=51-8x | | 10x-29=71 | | 76-4x=7+21 | | 4x-3*-3=7 | | 3x+13=39-5x | | 17x-17+31+9x-69-18x=-39 |

Equations solver categories